51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-677
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of an Accelerating, Pitching, Flat-Plate at Low Reynolds Number

Abstract: The understanding of low Reynolds number aerodynamics is becoming increasingly prevalent with the recent surge in interest in advanced Micro-Air Vehicle (MAV) technology. Research in this area has been primarily stimulated by a military need for smaller, more versatile, autonomous, surveillance aircraft. The mechanism for providing the high lift coe cient required for MAV applications is thought to be largely influenced by the formation of a Leading Edge Vortex (LEV). This paper analyses experimentally, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The study by [31], where TECS was dynamically actuated from 0 • to 30 • , addressed this particular question and found the transient lift/pitching moment response to be similar, whether the fore element was at an incidence of 0 • or 20 • . Investigations of the effect of actuation rates on the LEV size were also previously carried out by [33][34][35][36][37][38]. In these investigations, it was found that increasing the pitch rate delayed the formation of LEVs on the upper surface and made the LEVs more compact and stronger, thus producing a much larger transient C L .…”
Section: Effect Of Varying Actuation Ratesmentioning
confidence: 98%
“…The study by [31], where TECS was dynamically actuated from 0 • to 30 • , addressed this particular question and found the transient lift/pitching moment response to be similar, whether the fore element was at an incidence of 0 • or 20 • . Investigations of the effect of actuation rates on the LEV size were also previously carried out by [33][34][35][36][37][38]. In these investigations, it was found that increasing the pitch rate delayed the formation of LEVs on the upper surface and made the LEVs more compact and stronger, thus producing a much larger transient C L .…”
Section: Effect Of Varying Actuation Ratesmentioning
confidence: 98%
“…The system employs a CCD high-speed camera, which has a frame rate capability of more than 5x10 4 Hz, at a resolution of 1024 x 1024 pixels. The frame rate is selected to give a pixel displacement between images of between 2 and 5 pixels.…”
Section: High-speed Piv Systemmentioning
confidence: 99%
“…Stevens et al 4 used a simple kinematic argument to interpret PIV and flow visualisation data. For a wing pitched about the mid-chord, the development of the suction surface flow and the Leading Edge Vortex (LEV) was strongly correlated with the kinematics of the Leading Edge (LE), suggesting that the e↵ective local angle of incidence is of considerable significance in unsteady pitching motions.…”
Section: Introductionmentioning
confidence: 99%
“…Study of the vortex dynamics around plates undergoing unsteady motions has been identified as an international research task by the NATO AVT-202 Group and the AIAA Fluid Dynamics Technical Committee's Low Reynolds Number Discussion Group. The identified research task encompasses a wide variety of motions, including pitching 8,9 , rotation 10,11 , various acceleration profiles 12,13 , and the combination thereof 14 .…”
Section: Introductionmentioning
confidence: 99%